The borzoi practice book for writers - Hennessy, Michael (McGraw-Hill, 1993)
This book is specifically designed to accompany the BORZOI HAND BOOK FOR WRITERS, 3/e, but it is also available as a stand alone supplement. It engages students in exercises based in real discourse units. Sample writing from scientific, social science, humanities, popular journals and magazines, and student papers form the basis of this writing/work text